Analisis Strategi Pemasaran Mobil Merk Daihatsu Sigra pada PT. Armada International Motor Surabaya - Rizka Novianty Haninda; Ali Mahsun; Desia Ragil Saputro (Yos Soedarso Economic Journal (YEJ), 2021)
The author conducted this research at PT. International Motor Surabaya Fleet. The purpose of this research is to find out the strengths, weaknesses, opportunities and threats owned by the company and also to find out alternative strategies that can be used by the company, in this case PT. International Motor Surabaya Fleet. The research method used in this thesis is research in descriptive form with a qualitative approach. The data used are primary data and secondary data. Primary data is obtained from company leaders who are competent to provide information. Researchers collect information directly by conducting interviews. Secondary data was obtained from Daihatsu Sigra consumers or second informants, then from literature studies by studying various writings, books and theses related to this research. In describing the research results, the SWOT matrix is ​​used by analyzing internal and external factors which are carried out by providing an overview of the strengths, weaknesses, opportunities and threats that are owned by the company. Based on the results of the research analysis using the SWOT matrix which combines the strengths, weaknesses, opportunities and threats of the company, the matrix can produce four sets of possible alternative strategies. By using the SWOT analysis it can be obtained that the company can take alternative ST, WT, SO and WO strategies. Keywords: Qualitative; SWOT; Strategy; Competence.